ENACTIVE THEORY OF RADIOLOGY IMAGING: IMAGES AND LANGUAGE AS DIAGNOSTIC TOOLS - BRIEDIS, Mindaugas (Studia Universitatis Babeș-Bolyai Philosophia, 2018)
The article is based on research conducted at Le Bonheur Children’s Hospital, Radiology Department (Memphis, Tennessee, USA). It examines embodied cognition embedded in radiological diagnostics relating image perception with normative judgment constitution. The research follows the causal thesis in that it is possible to grasp categories and causality via visual experience (causal impressions) and language (causal verbs), which in turn heavily depends on strategies of the enaction of imaging technology and intersubjective corroboration. In this way, the pre-reflective and intersubjective constitution of categorial fulfillments of diagnostic experiences is disclosed by phenomenological ethnography of radiologists’ praxis showing how professional knowledge is structurally interrelated with certain kinesthetic and kinetic experiences, multilayered image apprehension and enactive metaphors.